Scheduling of Application for Siteplan Authorization Permit (Case of Licensing Process at Investment and Integrated Licensing Services Office in Sleman Regency) - Fitri Nugraheni; Vendie Abma; Sigit Yasien (Applied Research on Civil Engineering and Environment (ARCEE), 2020)
The permit process must comply with laws and regulations. The permit functions as controlling and supervising tool from the government of activities in certain cases based on the guidelines that must be implemented. The permit also functions as a disciplinarian and regulator in accordance with the law in the administration of government. In the process, several constrains or obstacles often occur in terms of the period of the process as well as technical and non-technical constrains. In this research, an analysis of the scheduling of the site plan permit approval process is based on field data related to the site plan permit approval process with the PERT method. The data used are primary data in the form of interviews and filling in the form of questions and secondary data in the form of a site plan approval process flow. The data that has been collected is then processed and analyzed in several stages. First, calculate the expected time period (te) using interview data and the results of filling in the expected time period (te), so that the expected time period for each activity will be found in accordance with the site plan approval process flow. Second, determine the dependency relationship between activities. In this stage, the relationship between each activity is determined. Third, create a network by changing the existing site authorization process flow into a form of network planning. The results of the schedule using the PERT method are a period of 38 days with alternatives that can be done to reach the time (Tx) of 18 working days in accordance with the Regent Regulations. In addition, the probability of the overall activity being completed is 0.8531 or 85.31%.